Menumbuhkan minat baca anak MI/SD dengan media buku bergambar seri - Lilis Sumaryanti (AL-ASASIYYA: Journal Of Basic Education, 2020)
Interest in reading Indonesian people, especially the level of MI/SD children is still relatively low because they prefer playing online games, watching television etc. This factor causes their ability to read is still lacking. In addition, there are reading books (both storybooks and textbooks) in school institutions that are still monotonous with colourless pictures so that children are easily bored and are not interested in reading them. Based on the above phenomenon, the reading interest of MI/SD children must be increased by the teacher because "books are a repository of knowledge and reading can open the horizons of the world". The use of learning media to foster children's interest in reading is with a picture book series. This series of picture books is more developed if the teacher dares to be creative by making colourful pictures equipped with simple sentences that can interest children to read them. This series picture book is effectively used in learning elementary school children because it contains games and also education. In the picture book series, there are several learning activities including observing, telling, reading and sorting pictures so that it becomes a complete story. Furthermore, teachers can add/collaborate on strategies or methods that can support the use of series picture books to be more innovative in each lesson.